Pengaruh Profitabilitas, Likuiditas, Solvabilitas dan Aktivitas terhadap Perubahan Harga Saham Perusahaan Subsektor Hotel dan Pariwisata yang Terdaftar di Bei Periode 2019-2021 - Reza Cikal Aditama; Muhammad Zaini (Universitas Batanghari, 2023)
This study aims to determine the effect of profitability, liquidity, solvency, and activity on the stock prices of hotel and tourism sub-sector companies listed on the IDX for the 2019-2021 period. The research method used is descriptive quantitative method, and the population used in this research is the hotel and tourism sub-sector companies that have been listed on the IDX. The sample selection technique uses the methodpurposive sampling. The number of samples obtained was 16 companies during the 2019-2021 period. Data collection is done by collecting annual reports and financial reports from the company's official website as well as the website www.idx.com . The data that has been collected is processed using the SPSS version 25 analysis tool with descriptive statistical test analysis methods, classical assumption tests, multiple linear regression analysis, coefficient of determination and hypothesis testing. The results of this study indicate that profitability (ROE) has a negative and significant effect on stock prices, liquidity (CR) has a negative and insignificant effect on stock prices, solvency (DER) has a positive and significant effect on stock prices, and activity (TATO) has a positive and no effect. significant to stock prices.